12-18 Yaş Arası Gençlerin Hedonik Tüketim Davranışlarının İncelenmesi: Kocaeli Şehir Merkezinde Bir Araştırma / Analysis of Hedonic Consumption Behaviours of the Young People Aged 12-18: A Research in the City Center of Kocaeli - ÇAKIR, MERVE; ÇAKMAK, ALİ ÇAĞLAR (Journal of History Culture and Art Research, 2012)
Günümüzde tüketiciler sadece ihtiyaçlarına yönelik alışveriş yapmayıp, duygusal anlamda haz duyabileceği ya da alışveriş esnasında zevk alabileceği alışverişler yapmaktadırlar. Modern tüketim toplumlarında tüketim olgusunun duygusal veya hissi boyutu ön plana çıkmış, satın alma sürecinde geleneksel anlayıştan belirgin derecede farklılıklar gösteren hedonik (hazcı) tüketim tüketici davranışları açısından giderek daha fazla oranda inceleme konusu olmaya başlamıştır. Pazarlama iletişiminde de firmaların hedef kitleleri genç tüketiciler olarak belirmektedir. Bu çalışma, genç tüketicilerin alışverişe bakışlarında gittikçe önemli bir yer alan hedonik tüketimin nedenlerini incelemeyi amaçlamaktadır. Analysis of Hedonic Consumption Behaviours of the Young People Aged 12-18: A Research in the City Center of Kocaeli At the present time, the consumers have not only been shopping just for their needs, but also for pleasure or to get a kick out of shopping. In modern consumption societies, the emotional dimension of consumption have come into prominence and the hedonic consumption at the process of purchasing that have significant differences from traditional mentality have increasingly been subject to researches. Also in marketing communication, the target audiences of the companies have appeared as young consumers. This study aims researching the reasons of the hedonic consumption which increasingly encompass an important place at the outlooking of the young consumers to shopping.